An Interactive Visual Auditory Multimedia Instructions for Toddlers - Puteri Noraisya Primandari; Elvianto Dwi Hartono; Siswoyo; Putri Rahayu Ningtyas (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2019)
Toddlers learn to use various ways to understand the meaning of words or sentences using symbols, spoken languages, pictures, sounds and various other five sensory functions. Nowadays, there have been many multimedia of children's learning developed in the community such as media for reading, writing, counting and others. All of the media which has been developed has not integrated all the components needed by children such as completely correcting the child's first reading or writing that need to be corrected. For this reason this research aim to develop interactive learning that combines all the elements that children needed by using a combination of pattern recognition, sound and images so that learning can be maximized and children's creativity is increased. Keywords— media, learn, toddlers